Pelatihan Petani dalam Produksi Pupuk Organik di Desa Tegalgede, Kecamatan Sumbersari, Kabupaten Jember - Rizal Perlambang CNAWP; Uyun Erma Malika (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Chemical fertilizers are increasingly rare and expensive, causing farmers (partners) to look for solutiosn by using organic fertilizer as a combination. However, a problem is currently being faced by partners, namely related to the production process of organic fertilizer made from goat manure. The characteristics of goat manure are hard, and it takes quite a long time to decompose, so farmers have to wait approximately one month before it can be applied as basic fertilizer on agricultural land. Efforts to speed up the decomposition process have been made by partners, namely by crushing or smoothing goat manure by pounding it manually. This stage requires quite a lot of time and energy, so it is felt to be less efficient. This is due to the lack of technology adopted in the partner environment. Based on the conditions and problems faced by partners, through this activity a solution will be offered in the form of technology for processing goat manure as raw material for organic fertilizer. This technology is in the form of a goat manure crushing machine to help speed up the decomposition process and provide nutrients, so that partners do not have to wait long for planting to start. This community service activity is carried out by providing counseling and training in making organic fertilizer from goat dung as raw material, accompanied by the use of a goat dung crushing machine. It is hoped that partners’ knowledge and skills can increase, especially in processing organic fertilizer made from goat manure.